SOVEREIGNTY V/S HUMAN RIGHTS: RECONCILING NATIONAL INTERESTS WITH INTERNATIONAL LEGAL OBLIGATIONS - Urooj Bashir; Syeda Mina Faisal; Dr Ishaq Ahmad, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
This article delves into the intricate balance between national sovereignty and the enforcement of international human rights obligations. It critically examines the tensions that arise when state interests and sovereignty clash with the mandates of international human rights law. Through a thorough analysis of key legal frameworks, case studies, and judicial decisions, the research illuminates how different countries navigate these conflicts. The article explores theoretical perspectives on sovereignty and human rights, evaluates the effectiveness of international oversight mechanisms, and assesses the role of global and regional human rights institutions. Additionally, it investigates the impact of political, cultural, and economic factors on states' compliance with international human rights norms. By offering a nuanced understanding of the reconciliation process between national interests and international obligations, this study aims to provide policymakers, legal practitioners, and scholars with insights into fostering a more coherent and just global human rights regime. The following article employs a qualitative research methodology.